Income Smoothing Practices Among Listed Firms in Malaysia - Mohamad, Nor Raihan (2001)
The income-smoothing phenomenon is well documented in accounting and finance literature. Although the existence of income smoothing practices have been detected in varying degrees across different samples, many issues relating to the practices of creative earnings management remain unresolved to date. However, the real danger is not that immoral management is busily engaged in these manipulative practices but the eroded confidence in the usefulness of financial accounting statements. The common issue of interest in previous income smoothing studies was the methodology or model selection used to identify the income smoothing sample fllll1s. Recent studies such as Albrect and Richardson (1990), Ashari et. al. (1994), Michelson et. al. (1995), and Carlson and Bathala (1997) adopted the income smoothing (IS) index model developed by Eckel (1981). This model is 'preferable' than the classical expectancy model because it mitigates the use of predicted earnings and the need to observe income smoothing behaviour over a long-term period. However, this model is unable to directly estimate the extent or amount of smothers and the direct instruments for income smoothing in firms. In addition, it heavily relies on several reasonable and general assumptions. Therefore, the mai on objective of this study is to verify the direct instruments used for income smoothing. The discretionary accounting changes and start-up costs (pre-operating and preliminary expenses) were observed and tested using the expectancy model to ascertain the extent of smoothing behavior. A start-up sample of 231 firms from the main and second board of the KLSE was analyzed for presence of smoothing behavior using an IS index model and expectancy model over a nine-year period (1990-1998). The analysis was divided into three different periods, from 1990 to 1996, from 1997 to 1998 and from 1990 to 1998 to isolate managerial behavior on smoothing during the pre-economic crisis and crisis period. The results from both models show higher percentage of smothers during the crisis period. This is consistent with the expectation that managers have strong motivation to smooth income during the economic crisis period to counter the fluctuation in reported income. The finding also shows that the expectancy model is more appropriate to identify income smoothing firms during the economic crisis period. The nonparametric test was performed to determine the final sample of smoothing firms. These sampled firms were further analyzed to determine the factors influencing income smoothing practices. Nine explanatory variables were tested and only three variables were found significant, namely, the profitability, debt financing and management ownership factor. The profitability and debt-financing factor have a negative relationship with income smoothing practices while the management ownership has a positive relationship. This implies that the firm with higher profit and greater level of debt has fewer tendencies to practice income smoothing. On the other hand, the manager-controlled firms are more likely to smooth income in a favorable way. These results suggest that principal-agent relationship and the profitability of a firm have strong impact on income smoothing behavior.